Analisis Implikatur Percakapan dalam Pembelajaran pada Mahasiswa IAIN Surakarta - Isnaniah, Siti (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2018)
Language plays an important role in communication domain. The role of a language would be an impact towards the receiver as the listener. In communication process, language is used as a mean of information exchange among humans. In addition, the language function speech out in different products. It means that there is an inconsistency between the speech and the meaning. This study actually would be discussing on speech implication. Speech implication concept is used to explain the differences appear between what was utterance and what was implicated. The method used in the research was qualitative descriptive. The place where the research conducted was IAIN Surakarta. The data source of the research were the informants; the situation, and the documents. The techniques of data collection were indepth interviewing, observation, and documents analysis. The sampling technique was purposive sampling. The data was analyzed by using the interactive analysis model. The results of the research were implication which is found on the speech, happen because the disorder of relevance maxim, quantity maxim, quality maxim, and maxim of way. Each implicate has its own certain objective and meaning by its speaker.Keywords: speech; implication; maxim.